2023
DOI: 10.1111/ases.13173
|View full text |Cite
|
Sign up to set email alerts
|

Effect of omentopexy/gastropexy on gastrointestinal symptoms after laparoscopic sleeve gastrectomy: A meta‐analysis of randomized controlled trials and systematic review

Abstract: Introduction The increased prevalence of obesity worldwide and low incidence of postoperative complications make the laparoscopic sleeve gastrectomy (LSG) a clear public choice for obese‐related individuals. Pre‐existing studies reported contentious outcomes regarding the association with gastrointestinal symptoms after adding omentopexy (Ome) or gastropexy (Gas) to LSG. The present meta‐analysis attempted to evaluate the pros and cons of operating Ome/Gas after LSG concerning gastrointestinal symptoms. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…When a passage disturbance is caused by a stenosis or a twisting distal to the leak site, increased intragastric pressure can make it difficult for the leak site to heal. Therefore, suturing the gastric tube to the mesentery or abdominal wall during reoperation is advisable in preventing such complications [15]. Enteral nutrition has also been reported to accelerate leak healing.…”
Section: Initial Treatments For Sleeve Leakagementioning
confidence: 99%
“…When a passage disturbance is caused by a stenosis or a twisting distal to the leak site, increased intragastric pressure can make it difficult for the leak site to heal. Therefore, suturing the gastric tube to the mesentery or abdominal wall during reoperation is advisable in preventing such complications [15]. Enteral nutrition has also been reported to accelerate leak healing.…”
Section: Initial Treatments For Sleeve Leakagementioning
confidence: 99%
“…Apart from staple line reinforcement, omentopexy is another type of reinforcement technique, which uses sutures to fix the rest of the stomach to the free edge of the greater omentum [21]. The effect of SG with omentopexy on the rate of postsurgery complications was investigated in 3 systematic reviews [22][23][24], which reported inconsistent results. Of the 3 reviews, 2 [22,24] suggested that SG with omentopexy outperforms SG without omentopexy in reducing gastrointestinal adverse reactions (eg, nausea, reflux, and vomiting), while in terms of reducing gastric leakage, they showed the opposite effects.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of SG with omentopexy on the rate of postsurgery complications was investigated in 3 systematic reviews [22][23][24], which reported inconsistent results. Of the 3 reviews, 2 [22,24] suggested that SG with omentopexy outperforms SG without omentopexy in reducing gastrointestinal adverse reactions (eg, nausea, reflux, and vomiting), while in terms of reducing gastric leakage, they showed the opposite effects. Opposing results were also observed in 2 reviews [23,24] in terms of the length of hospital stay.…”
Section: Introductionmentioning
confidence: 99%